Organochlorines in Antarctic and Arctic Avian Top Predators: A Comparison between the South Polar Skua and Two Species of Northern Hemisphere Gulls - Bustnes, Jan O; Tveraa, Torkild; Henden, John A; Varpe, Øystein; Janssen, Kirstin; Skaare, Janneche U (Environmental Science & Technology, 2006)
Different organochlorine compounds (OCs) were measured in the blood of breeding south polar skuas (Catharacta maccormicki) at Svarthamaren, Dronning Maud Land (Antarctica) and compared to those in two species of northern hemisphere gulls: the Arctic glaucous gull (Larus hyperboreus) and the subarctic great black-backed gull (Larus marinus). The skuas had 8% and 29% of the ∑OC levels (45 ng/g, wet weight) of glaucous gulls (591 ng/g) and great black-backed gulls (158 ng/g), respectively. Polychlorinated biphenyls (PCBs) and p,p‘-dichlorodiphenyldichloroethylene (p,p‘-DDE) were very low in skuas compared to northern gulls, but the mean hexachlorobenzene (HCB) level was 1.7 times higher than in great black-backed gulls and one-third of the glaucous gull level. Mirex levels in skuas were among the highest reported in birds, the mean level being 3 and 26 times higher than those in glaucous gull and great black-backed gulls, respectively. In skuas, the mean levels of HCB, oxychlordane, p,p‘-DDE, and PCBs increased by about 30% during a 2-week period, and mirex increased by nearly 60%. In glacuous gulls, HCB, p,p‘-DDE, and PCBs increased by 10−20%. For HCB, mirex, and oxychlordane, only a relatively small proportion of the increase in skuas could be explained by changes in lipid pools and the levels at first sampling, compared to glaucous gulls. Thus, skuas were probably accumulating these compounds when present in Antarctica. p,p‘-DDE and PCB levels, in contrast, seemed much more stable in the skuas. Relatively high levels of mirex and HCB in south polar skuas are concerning with regard to potential adverse effects.
Publisher: American Chemical Society
Keywords: Dronning Maud Land; kjemiske analyser; ornitologi; polarområdene; sjøfugler

Hierarchical Patch Dynamics and Animal Movement Pattern - Fauchald, Per; Tveraa, Torkild (Oecologia, 2006)
In hierarchical patch systems, small-scale patches of high density are nested within large-scale patches of low density. The organization of multiple-scale hierarchical systems makes non-random strategies for dispersal and movement particularly important. Here, we apply a new method based on first-passage time on the pathway of a foraging seabird, the Antarctic petrel (Thalassoica antarctica), to quantify its foraging pattern and the spatial dynamics of its foraging areas. Our results suggest that Antarctic petrels used a nested search strategy to track a highly dynamic hierarchical patch system where small-scale patches were congregated within patches at larger scales. The birds searched for large-scale patches by traveling fast and over long distances. Once within a large-scale patch, the birds concentrated their search to find smaller scale patches. By comparing the pathway of different birds we were able to quantify the spatial scale and turnover of their foraging areas. On the largest scale we found foraging areas with a characteristic scale of about 400 km. Nested within these areas we found foraging areas with a characteristic scale of about 100 km. The large-scale areas disappeared or moved within a time frame of weeks while the nested small-scale areas disappeared or moved within days. Antarctic krill (Euphausia superba) is the dominant food item of Antarctic petrels and we suggest that our findings reflect the spatial dynamics of krill in the area.
Publisher: Springer
Keywords: Dronning Maud Land; NARE ekspedisjoner; fugler; ornitologi; petreller; satellittelemetri; zoologi